2008
DOI: 10.1007/s11743-008-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies on the Interfacial and Bulk Behaviors of Sodium N‐Dodecanoyl Sarcosinate (SDDS)

Abstract: Sodium N-dodecanoyl sarcosinate (SDDS), a novel amino-acid based surfactant, has immense biological and industrial importance. Although it is being used in a number of cosmetic formulations, systematic analysis of the bulk and interfacial properties of the surfactant is scarce in the literature. In this study, effects of salt, temperature, and pH on the self-association and related properties of SDDS have been examined in detail using methods such as tensiometry, conductometry, fluorimetry, pH-metry, spectroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 47 publications
4
59
0
Order By: Relevance
“…The increase in thermal energy due to the rise in temperature enhances the ionization of the ionic surfactant SDS and, thereby, an increase in b with temperature is obvious. Similar results have also been reported for the variation of CMC and b for SDS in presence and absence of additives in aqueous medium by others [22,30]. In the presence of the additives amino acids/ peptide, the values of degree of ionization, b are found to increase from Gly to Gly-Gly.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The increase in thermal energy due to the rise in temperature enhances the ionization of the ionic surfactant SDS and, thereby, an increase in b with temperature is obvious. Similar results have also been reported for the variation of CMC and b for SDS in presence and absence of additives in aqueous medium by others [22,30]. In the presence of the additives amino acids/ peptide, the values of degree of ionization, b are found to increase from Gly to Gly-Gly.…”
Section: Resultssupporting
confidence: 89%
“…The effect of temperature on the CMC of surfactant in aqueous medium is complex [34]. In general, the effect of temperature on the CMC of surfactants in aqueous medium is analyzed in terms of two opposing effects [22,30,34]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on integrity of this method was verified by Kale et al [67] and also by Bandyopathyay and Moulik [68] who have estimated g by using ion-selective membrane electrode and found that the values of g thus obtained are in good agreement with those obtained conductometrically. Hence the degree of counterion dissociation (g) is experimental technique dependent [69], like cmc [70,71]. Counterions are bound primarily by the electric field created by head group and also by specific interactions that depend upon the head group and counterion type.…”
Section: Thermodynamics Of Micellizationmentioning
confidence: 99%
“…Both, SLS and SDBS are superior to conventional surfactants due to their attractive applications in cosmetics and pharmaceutical formulations. SLS, amino acid based anionic surfactant is a derivative of sarcosinate and offers many biological as well as industrial uses [18][19][20]. SDBS also possess numerous applications like, it act as a suitable template for the synthesis of nanoparticles and nanotubes, host for entrapping environmental hazardous substances, bio compatible as it desorbs many harmful organic compounds from soil and improves the efficiency of soil [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%